2020
DOI: 10.3171/2020.4.spine191303
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the correlation between preoperative cervical degeneration and postoperative heterotopic ossification after cervical disc replacement: minimum 10-year follow-up data

Abstract: OBJECTIVEThe authors aimed to identify factors that may be useful for quantifying the amount of degenerative change in preoperative patients to identify ideal candidates for cervical disc replacement (CDR) in patients with a minimum of 10 years of follow-up data.METHODSDuring the period from December 2003 to August 2008, 54 patients underwent CDR with a Bryan cervical disc prosthesis performed by the same group of surgeons, and all of the patients in this group with at least 10 years of follow-up data were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(27 reference statements)
0
12
0
Order By: Relevance
“… 19 , 44 Preoperative cervical degeneration, including osteophyte formation and facet joint degeneration, are considered as relative contraindications for disc replacement, because it may be related to poor postoperative ROM and heterotopic ossification (HO). 45 , 46 Although we excluded patients with severe facet joint degeneration not suitable for CDA, facet asymmetry may still be associated with some potential degeneration, which could also result in decreased ROM after CDA surgery. However, no significant progression of facet joint degeneration was observed during the 2-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 44 Preoperative cervical degeneration, including osteophyte formation and facet joint degeneration, are considered as relative contraindications for disc replacement, because it may be related to poor postoperative ROM and heterotopic ossification (HO). 45 , 46 Although we excluded patients with severe facet joint degeneration not suitable for CDA, facet asymmetry may still be associated with some potential degeneration, which could also result in decreased ROM after CDA surgery. However, no significant progression of facet joint degeneration was observed during the 2-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant number of class III devices were pertinent to spine surgery, only one performed a subgroup analysis that resulted in significant outcome differences between men and women (a greater proportion of women had heterotopic ossification after the implantation of the Bryan cervical disk arthroplasty). 8,28,29 It was hypothesized that this was a result of less spinal stability in women, possibly due to hormonal differences resulting in differences in skeletal growth and maturation. 8,28 In addition, both the Cormet and Conserve Plus Hip Resurfacing Systems were shown to have worse outcomes in women because of greater rates of revision surgery and implant failure, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The endplate sclerosis is distinguished among no apparent sclerosis, just detectable and definite sclerosis according to the degree of detectability. 10,17 The uncovertebral joint was assessed preoperatively using the coronal reconstruction computed tomography (CT) to identify osteophytes at the uncovertebral joint area. Facet joint degeneration was evaluated using a computed tomographic grading system reported by Park et al 11 (grade 1-4), with higher grade denoting more advanced degree of degeneration.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al 6 reported that the rate of HO formation was significantly higher in patients with spondylosis compared to that with soft-disc herniations. In recent years, several qualitative or quantitative studies confirmed the degree of degeneration in the surgical level was positively correlated with postoperative HO, [7][8][9][10] whilst some studies found preoperative degenerative changes exert no significant influence on the occurrence of HO. 11,12 However, few studies investigated the effect of all the components of cervical spondylosis on HO.…”
Section: Introductionmentioning
confidence: 99%